2020
DOI: 10.1001/jamanetworkopen.2020.26506
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Leisure Time Physical Activity and Brain Health in a Multiethnic Cohort of Older Adults

Abstract: IMPORTANCE Results from longitudinal studies suggest that regular leisure time physical activity (LTPA) is associated with reduced risk of dementia or Alzheimer disease. Data on the association between LTPA and brain magnetic resonance imaging (MRI) measures remain scarce and inconsistent. OBJECTIVE To examine the association of LTPA and MRI-assessed brain aging measures in a multiethnic elderly population. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study included 1443 older (Ն65 years) adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 50 publications
0
28
0
2
Order By: Relevance
“…Meta-analyses indicated that physical activity was associated with better outcomes for HDL, GM and brain activation, but not for LDL and Aβ. Narrative syntheses revealed that one of three studies demonstrated an association between physical activity and WM volume (Gu et al, 2020); one study reported an association between physical activity and WM integrity (Smith et al, 2016); one of two studies demonstrated an association between physical activity and cerebrovascular health (Boots et al, 2015); and two of two studies reported an association between physical activity and functional connectivity (Kerestes et al, 2015;de Frutos-Lucas et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meta-analyses indicated that physical activity was associated with better outcomes for HDL, GM and brain activation, but not for LDL and Aβ. Narrative syntheses revealed that one of three studies demonstrated an association between physical activity and WM volume (Gu et al, 2020); one study reported an association between physical activity and WM integrity (Smith et al, 2016); one of two studies demonstrated an association between physical activity and cerebrovascular health (Boots et al, 2015); and two of two studies reported an association between physical activity and functional connectivity (Kerestes et al, 2015;de Frutos-Lucas et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…From the three studies which assessed WM volume, four of the six effect sizes for e4 carriers and non-carriers were not reported, and neither were their physical activity main effects. One study (Gu et al, 2020) only reported stratified APOE data and showed significant positive associations between physical activity and WM volume for both e4 carriers and non-carriers. Highly active e4 carriers had 17.5 cm 3 higher WM volume compared to inactive e4 carriers, whereas active non-carriers had 31.6 cm 3 higher WM volume compared to inactive non-carriers.…”
Section: White Matter Volumementioning
confidence: 99%
See 2 more Smart Citations
“…using similar study procedures. 6,26 Briefly, participants were recruited from a probability sample of Medicare recipients who were 65 years of age or older, socioeconomically and racially diverse, and residing in northern Manhattan. At the study entry, each subject underwent a structured in-person interview of general health and function, followed by a comprehensive assessment including medical and neurological histories, and standardized physical, neurological, and neuropsychological examinations.…”
Section: Highlightsmentioning
confidence: 99%